2016
DOI: 10.1016/j.bpj.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of a Globally Connected Contractile Network in a Microtubule-Motor System

Abstract: Microtubule (MT) networks play key roles in cell division, intracellular transport, and cell motility. These functions of MT networks occur through interactions between MTs and various associated proteins, notably motor proteins that bundle and slide MTs. Our objective in this study was to address the question of how motors determine the nature of MT networks. We conducted in vitro assays using homotetrameric kinesin Eg5, a motor protein involved in the formation and maintenance of the mitotic spindle. The mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 73 publications
6
63
1
Order By: Relevance
“…While the role of cross-linking has been well described in terms of controlling force transmission (13,14,(21)(22)(23), our work suggests that it also plays an important role in controlling the direction of the deformation, namely changing it from extensile to contractile. This result unifies previous observations of both extensile and contractile behaviors in active microtubule systems (6,7,(17)(18)(19)(20), suggesting that network connectivity is a significant factor in determining which behavior predominates. In future work, it will be interesting to explore the transitions between other microscopic deformation modes in active motor-filament systems and see how these are controlled by local structure or composition (e.g., filament orientation or polarity organization).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While the role of cross-linking has been well described in terms of controlling force transmission (13,14,(21)(22)(23), our work suggests that it also plays an important role in controlling the direction of the deformation, namely changing it from extensile to contractile. This result unifies previous observations of both extensile and contractile behaviors in active microtubule systems (6,7,(17)(18)(19)(20), suggesting that network connectivity is a significant factor in determining which behavior predominates. In future work, it will be interesting to explore the transitions between other microscopic deformation modes in active motor-filament systems and see how these are controlled by local structure or composition (e.g., filament orientation or polarity organization).…”
Section: Discussionsupporting
confidence: 90%
“…Experimentally, in vitro networks constructed from actin filaments and myosin II motors are robustly contractile (13)(14)(15)(16). By contrast, systems of microtubules and molecular motors are either extensile (6,7,17,18) or contractile (19,20). One difference between these two active materials is that microtubules are significantly more rigid than actin.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, we used −1 = 3.16 which corresponds to ~15 min in reality. This is comparable with the observed time scale of MT bundle dynamics in vitro [39]. In addition, we set = following the model for actin filament in [12].…”
Section: Mathematical Model For Bb Pattern Formation In Multi-ciliatesupporting
confidence: 72%
“…Several recent high profile studies expanded upon this theme and demonstrated filament/motor systems exhibiting self-organization, ranging from networks formed by actin filaments and myosin motors, 119, 120 over vortex lattices emerging from microtubules moving on surface-adhered motors, 94, 97, 121 to microtubule bundle networks exhibiting motion and internal flows driven by kinesin motors. 74, 77118, 122 …”
Section: Non-equilibrium Self-assembly and Self-organization Of Micromentioning
confidence: 99%
“…(b) Different microtubule networks form depending on the concentration of motile cross-linkers (here the kinesin Eg5). Adapted from 118 . (c) Kinesin cross-linkers and depletion forces lead to the self-organization of microtubules into beating cilia.…”
Section: Figurementioning
confidence: 99%